Resignifying the Teaching Role: Challenges in Linking Teaching With the Current Historical Context - Robles-Murillo, Keylor (Revista Electrónica Educare, 2020)
This essay’s main objective is to provide reflections on the following generating theme: “The teacher of today: someone who informs, inspires and educates.” Therefore, the proposed axis and title articulate ideas based on the relationship between didactics and the current context. Regarding medical issues, they are (a) the need to link the curricular contents with reality and the particular context in which each person who takes part in the educational process is located, and (b) the importance of vocation in teaching practice and the role of self-criticism as part of the feedback. The challenges identified are related to these three aspects: a) critical reflection; b) breaks with traditional paradigms; and c) teacher mediation. Finally, collective strategies to confront them are proposed, which are based on research, constructivism, and reflexive, horizontal, and dialogical planning.